2022
DOI: 10.3389/fpls.2022.889494
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cytogenetic Identification of a New Wheat-Rye 6R Addition Line and Physical Localization of Its Powdery Mildew Resistance Gene

Abstract: Rye (Secale cereale L.), a naturally cross-pollinating relative of wheat, is a tertiary gene donor and of substantial value in wheat improvement. Wheat powdery mildew is caused by Blumeria graminis f. sp. tritici (Bgt), which seriously affects yield and quality worldwide. Identifying and transferring new, effective resistance genes against powdery mildew from rye is important for wheat breeding. The current study developed a wheat-rye line YT2 resistant to powdery mildew by crossing, backcrossing, and self-pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 76 publications
1
20
0
Order By: Relevance
“…When a resistance gene was identified, less linkage drag is the critical factor associated with its easy use in wheat breeding programs, but often, disease resistance is at the expense of some agronomic traits and reduced plant adaptation (Deng et al, 2017 ; Ma et al, 2018 ; Han et al, 2022b ). Fortunately, YN99102 is an elite derivative line from the same breeding process as a famous wheat cultivar Yannong 999 in China, which is the first wheat cultivar to exceed 800 kilograms per mu yield in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When a resistance gene was identified, less linkage drag is the critical factor associated with its easy use in wheat breeding programs, but often, disease resistance is at the expense of some agronomic traits and reduced plant adaptation (Deng et al, 2017 ; Ma et al, 2018 ; Han et al, 2022b ). Fortunately, YN99102 is an elite derivative line from the same breeding process as a famous wheat cultivar Yannong 999 in China, which is the first wheat cultivar to exceed 800 kilograms per mu yield in China.…”
Section: Discussionmentioning
confidence: 99%
“…PCR amplification was performed as described by Han et al ( 2022a , b ) with minor modification. The PCR products were then separated in 8% non-denaturing polyacrylamide gels with a 29:1 ratio of acrylamide and bisacrylamide, finally visualized by silver staining.…”
Section: Methodsmentioning
confidence: 99%
“…Several other 6R chromosomes have been introduced into the wheat genome. For example, Han et al (2022) reported a 6R addition line originating from a cross between octoploid triticale and common wheat that exhibited resistance to powdery mildew. Duan et al (2022) reported a T6RL.6BS translocation line with 2018) reported a 6RL/6D small segment translocation line with powdery mildew resistance that originated from rye Kustro.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 10 years, several new 1RS chromosomes have been introduced into the wheat genome and have exhibited resistance to the new Pst and Bgt pathogens (Ren et al, 2017a(Ren et al, , 2018(Ren et al, , 2022Han et al, 2020). Additionally, 2R, 4R, 5R, 6R, and 7R chromosomes are also introduced into the wheat genome in the form of chromosome translocation, addition, and substitution, and several of these newly developed lines exhibit resistance to stripe rust or powdery mildew (An et al, 2015(An et al, , 2019Li et al, 2016;Schneider et al, 2016;Ren et al, 2017bRen et al, , 2020Johansson et al, 2020;Han et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the coevolution of pathogen virulence with host resistance and the rapid emergence of new virulent isolates, however, most powdery mildew resistance genes deployed in large-scale commercial production have successively lost their effectiveness against the pathogen [ 4 , 13 ]. A typical example is the “boom–bust” of Pm8 derived from chromosome arm 1RS of Petkus rye, which has triggered continual severe epidemics of powdery mildew in the main wheat production regions of China [ 14 , 15 ]. The discovery, identification, and deployment of additional sources of powdery mildew resistance in wheat-related germplasm to address this vulnerability is therefore urgently needed for breeding new resistant wheat cultivars [ 16 ].…”
Section: Introductionmentioning
confidence: 99%